Fertilizer Management for Maximizing Soybean (Glycine max L.) Production in Char Lands of Bangladesh - Chowdhury, M M U; Farhad, I S M; Bhowal, S K; Bhowmik, S K; Choudhury, A K (The Agriculturists, 2015)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> An experiment was conducted at Char Martin under Multi Location Testing site in Laxmipur district during Rabi season of 2011-12 & 2012-13 with different fertilizer doses to find out the economic fertilizer dose for soybean variety BARI Soybean 6 under farmers field condition. Four fertilizer combinations viz; T1 : 17-27-55-2.7-2.0-0 kg ha-1 of N-P-K-S-Zn-B (Soil Test Based fertilizer), T2 : 25- 25-50-10-0-0 kg ha-1 of N-P-K-S-Zn-B (Fertilizer Recommendation Guide, 2005 based fertilizer), T3 : 28-13-0-0-0-0 kg ha-1 of N-P-K-S-Zn-B (Farmers practice) and T4: Native fertility (control) were selected. All the yield and yield contributing characters of BARI Soybean 6 varied significantly with the different fertilizer treatments. The highest seed yield (2.99 t ha-1) was recorded from plants treated with T1 which was statistically similar to T2. The lowest seed yield (1.74 t ha-1) was obtained from T4. The highest gross return (Tk.104650 ha-1), net return (Tk. 56375 ha-1) and benefit cost ratio (2.16) were obtained from T1 and the lowest gross return (Tk. 60900 ha-1), net return (Tk.19900 ha-1) and BCR (1.48) was obtained from T4 . <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'Times New Roman'; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The Agriculturists <span style="font-size: 11.0pt; font-family: 'Calibri','sans-serif'; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: 'Times New Roman'; mso-fareast-theme-font: minor-fareast; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">2014; 12(2) 98-102 <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>